GROWTH CHARACTER DIVERSITY OF LOCAL CULTIVAR SORGHUM (Sorghum bicolor (L.) Moench)IN EAST NUSA TENGGARA, INDONESIA - Tnunay, Ite Morina Yostianti; Chikmawati, Tatik; Miftahudin, Miftahudin (SAINSTEK, 2019)
ABSTRAK Sorghum is a crop plant that has great potential to be developed in marginal land especially in East Nusa Tenggara. However, information about growth character as one of indicator for sorghum cultivation was very limited. This research aimed to describe growth character variation of local cultivar sorghum in East Nusa Tenggara. The exploration and sample collection were conducted in 3 islands, i. e.: Timor, Sumba and Flores. Growth character were analyzes using Analysis of Variance One Way at 95% confidence level. The result showed that 29 accessions of local cultivar sorghum in East Nusa Tenggara varied in 12 growth characters. The characters are plant heigh per week, internode number, internode length, leaf surface area, flowering time, spike number per panicle, node number per panicle, sessile spikelet number, pedicelled spikelet number, seed number per plant, seed water content, and 100 seeds weight. Keywords: East Nusa Tenggara, Local Cultivar Sorghum